Principle of ultrasound. Ergonomics in point-of-care ultrasound. - Mohd Fathil, Shahridan; Yeoh, Jie Cong; Lee, Kee Choon; Lim, See Choo; Mazlan, Mohamed Muhazan; Shamsudin, Nurul Shaliza; Abd Ghani, Muhamad Rasydan (Springer, 2024)
Work is where ergonomics got its start; the Greek term ergon means “work”. Workplace ergonomics is the study and practice of improving productivity and worker safety via the optimal layout of facilities, tools, and personnel.